2009
DOI: 10.1159/000219316
|View full text |Cite
|
Sign up to set email alerts
|

Test of a Homeopathic Dilution of Aconitum napellus

Abstract: Background: Although healthy persons often report on reactions to homeopathically diluted substances, the mechanism behind such reactions remains unclear. This study examines whether a distinction can be made between the short-term reactions of healthy volunteers to a homeopathically diluted substance – Aconitum napellus C30 – and to a placebo. Participants and Methods: From the 33 subjects randomized for this double-blind, placebo-controlled crossover study, 27 could be included in the analysis. The study com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In 1 trial, reactions of healthy volunteers towards ac30c globules were assessed in a randomised, double-blind, controlled crossover study, and were significantly different from reactions after placebo intake [17]. In the other trial, the effectiveness of cq6x in patients with restless leg syndrome was examined (L. Rist, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In 1 trial, reactions of healthy volunteers towards ac30c globules were assessed in a randomised, double-blind, controlled crossover study, and were significantly different from reactions after placebo intake [17]. In the other trial, the effectiveness of cq6x in patients with restless leg syndrome was examined (L. Rist, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Following Mexican homeopathic regulations and starting from the original mother tincture – an ethanolic extract in this case – several dynamizations/succussion (shaking by forceful striking) and serial dilutions in distilled water were performed to obtain 6 th (6C) and 30 th (30C) dilutions. (Note: Acn 30C is a common dosage used in homeopathy[18] and there have been no reported adverse effects from homeopathic remedies above 12C. )[39] The final solutions contained A. napellus , all in decimal dilutions of Hahnemann (dH) in distilled water, were colorless and odorless, and had a 1% alcohol concentration.…”
Section: Methodsmentioning
confidence: 99%
“…[1617] A double-blind crossover study in 27 healthy volunteers found a difference in reported responses (short-term signs and symptoms) when treated for 3 days with Acn 30 C versus placebo, indicating that Acn at that dose had a recognizable effect. [18]…”
Section: Introductionmentioning
confidence: 99%
“…The effects of homeopathic preparations of aconite were also studied on humans [21,22]. Although healthy people often report a reaction to homeopathic remedies, the mechanism of such reactions remains unclear.…”
Section: Efficacy Profile Of the Homeopathic Productmentioning
confidence: 99%
“…Although healthy people often report a reaction to homeopathic remedies, the mechanism of such reactions remains unclear. A study was carried out to investigate the differences between short-term effects of the homeopathic preparation Aconitum napellus C30 and placebo on healthy volunteers [22]. Of 33 randomly selected subjects for this doubleblind, placebo-controlled, cross-study, 27 were included in the analysis.…”
Section: Efficacy Profile Of the Homeopathic Productmentioning
confidence: 99%